“Danke Deutschland!” - Udovič, Boštjan (Acta Histriae, 2022)
The article analyses Slovenian–German relations, with a particular focus on the period between December 1990 and June 1991. The author takes a look at the positions that the Federal Republic of Germany assumed with regard to the plebiscite in Slovenia and recognition of Slovenian independence, as well as the circumstances (national and international) that led Germany to these positions. The article finds that as late as the spring of 1991 the official German policy was preserving the integrity of Yugoslavia, while it was already aware this might be an unrealistic wish. This is why it foresaw Slovenian and Croatian independence as one of the possibilities. When war in Slovenia broke out, Germany saw that Yugoslavia was gone, so it took a completely different stance than only weeks before. This was also reflected in its active engagement for swift international recognition of Slovenia and Croatia.
Keywords: Diplomacija; osamosvojitev Slovenije; slovensko-nemški odnosi; Suverenost; Zvezna republika Nemčija